In Situ Research on the Spatiotemporal Variations in the Temperature and Deformation of Aeolian Sand-Modified Soil Roadbed Constructed in Cold Regions. (12th August 2022) - Li, Gao; Zhou, Fubiao; Su, Zhandong; Bo, Jingshan; Chen, Xiang; Li, Chi
Abstract : Aiming at the cracking phenomenon of an aeolian sand-modified soil roadbed in an actual project near Tongliao city in eastern Inner Mongolia, Northeast China, an in situ test was conducted. Temperature-compensated fiber Bragg grating (FBG) strain sensors and moisture sensors were embedded into the test roadbed to monitor and observe the relationships between the temperature, moisture, and deformation of the roadbed with respect to variations in climate conditions in such a cold region. For the core issues of roadbed soil deformation and impact on the project, two climate conditions, namely, temperature and rainfall, were taken as external factors, while the temperature and moisture of the roadbed soil were taken as internal factors controlling the deformation and failure of the roadbed soil. A correlation analysis of the test roadbed monitoring data showed that the roadbed soil moisture was weakly affected by environmental conditions. The roadbed soil temperature was independent of the rainfall but was significantly related to air temperature variation (the correlation coefficient ranged from 0.6301 to 0.8926). Limited by the boundary conditions of the roadbed, the response of the variation in the roadbed soil temperature to the air temperature variation gradually weakened from the shallow surface to the deeper parts and the lag in the roadbed soil temperature variation relative to the air temperature variation became more evident. A correlation analysis of the monitoring data of the roadbed soil deformation, soil temperature, and soil moisture showed that the roadbed soil moisture had a weak correlation with the roadbed soil temperature. The roadbed soil deformation was independent of the soil moisture but was strongly related to the roadbed soil temperature. Therefore, the strain of the test roadbed could reflect the roadbed deformation as temperature deformation. The temperature deformation of the roadbed superficial soil was significantly greater than that of the deep soil.